A Formula for Total Savings - Anderson, Montgomery D. (Quarterly Journal of Economics, 1943)
I. Confusion in translating the concept "saving" into concrete statistical measurement, 106. — II. Saving vs. investment, 108. — III. Measuring the rate of saving, 111. — IV. Relation between saving and investment, 113. — Statistical verification, 116. — Advantages of selecting the typical accounting period as the time interval, 116. — V. No confusion with hoarding, 119.— The "producer-consumer investment ratio, " 119.